PENGARUH MEDIA FLIP CHART TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DITK B PAUD TUNAS BANGSA KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Khotimah, Khusnul; ', Zulkifli; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on an observation, pupils’ speaking ability that are not showing optimal development yet. So it is necessary to use flip chart media. This study aims to know the effectiveness of flip chart media against speaking ability of children ages 5-6 years in TK B PAUD Terpadu Tunas Bangsa. The sample of this study was 30 pupils which were divided into two classes, the experimental class and the control class. The data collection technique was observation. The data analysis technique was using t-test that using SPSS 20 program. The hypothesis is the flip chart media usage activity can influence the speaking ability of 5-6 years in TK B PAUD Terpadu Tunas Bangsa. It can be known from the data analysis on the comparison pretest and posttest the experimental class obtained t count =12,093 and sig. (2-tailed)=0.000. Since sig. (2-tailed)=0.000<0,05,, it can be concluded that there is a significant influence after using flip chart media in learning process. So, it means Ho is rejected and Ha is accepted that means there is a very significant influence flip chart media on the speaking ability of children which is in the experimental class. The influence of flip chart media against speaking ability children ages 5-6 years in TK B PAUD Terpadu Tunas Bangsa is 68,95%Keywords: Speaking Ability, Game Board of Guess Word.